Orden dentro del desorden: circulación de libros de derecho en Nueva España, 1585–1640 - Idalia García (Rechtsgeschichte - Legal History)
Law books circulated widely in New Spain; we ﬁnd evidence of them both in the private libraries of Crown officials and in the institutional libraries of religious orders. The books were either trans- ported from Europe or acquired in New Spanish cities, where they were available due to the commercial networks established by booksellers from the 16th century onwards. These books contributed to the recreation of a Western normative order in American societies and thus played a key role in the emergence of a new legal culture. The identiﬁcation of the speciﬁc editions used by readers in New Spain requires the analysis both of historical documents and of the books themselves, as far as these are extant. However, this evidence cannot help us answer a number of crucial questions regarding the signiﬁcance and use of these books: which books were fundamental in establishing a normative order in the Viceroyalty of New Spain? What was seen as a law book at that time? Indeed, what different kinds and genres of books can be considered legal literature? These questions do not have simple answers, but rather require us to consider also other aspects, such as the contemporary understanding of what constituted typical »jurists’ books« during the Ancien Régime, and whether their presence in the collections of oidores, judges, prosecutors and lawyers actually reﬂected these officials’ legal practice. In order to approach these questions, this article analyses the earliest extant lists of books from the viceregal period, drawn up between 1585 and 1640. These book lists were prepared in the context of the inquisitorial control over the circulation of books within the Spanish empire and provide us with information on the ﬁrst wave of books that entered New Spain.